Cultural Literacy and Youth Participation in Preserving Local Culture: An Empirical Study among Young Generations in Indonesia - Yandira Arizki Fatiha; Ebyghael Joito Nababan; Destri Natalia Telaumbanua; Mahfuzi Irwan (Parpudi: Journal Of Community and Adult Learning, 2025)
The preservation of local culture faces increasing challenges amid globalization, digitalization, and shifting youth lifestyles. Cultural literacy plays a crucial role in shaping young people’s awareness, attitudes, and participation in safeguarding cultural heritage. This study aims to analyze the level of cultural literacy and the extent of youth participation in preserving local culture. A quantitative descriptive approach was employed, involving young respondents aged 18–25 years. Data were collected using a structured questionnaire measuring cultural literacy dimensions—cultural knowledge, cultural awareness, critical understanding, and cultural participation. The findings indicate that most respondents demonstrate moderate to high levels of cultural literacy, particularly in cultural awareness and symbolic understanding. However, active participation in cultural preservation activities remains relatively limited and tends to be symbolic rather than practical. The results suggest that while young people possess basic cultural knowledge, gaps persist between cultural understanding and concrete participatory actions. Strengthening cultural literacy through education, digital media engagement, and community-based cultural programs is essential to foster sustainable youth participation in local cultural preservation.